2017
DOI: 10.1186/s12936-017-1711-5
|View full text |Cite
|
Sign up to set email alerts
|

Increase in imported malaria in the Netherlands in asylum seekers and VFR travellers

Abstract: BackgroundMalaria is a notifiable disease in the Netherlands, a non-endemic country. Imported malaria infections occur regularly among travellers, migrants and visitors. Surveillance data were analysed from 2008 to 2015. Trends in amounts of notifications among risk groups were analysed using Poisson regression. For asylum seekers, yearly incidence was calculated per region of origin, using national asylum request statistics as denominator data. For tourists, denominator data were used from travel statistics t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 18 publications
4
18
0
Order By: Relevance
“…Malaria is no longer endemic in Italy since 1970 when the WHO officially declared Italy malaria-free where nowadays is the most commonly imported disease [ 6 , 20 , 24 , 25 ]. The risk of imported malaria depends on malaria endemicity at the destination, the number and the behavior (adherence to personnel protective measures) of the travellers to risk areas, adequate use of chemoprophylaxis, and efforts for vector control around the accommodation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malaria is no longer endemic in Italy since 1970 when the WHO officially declared Italy malaria-free where nowadays is the most commonly imported disease [ 6 , 20 , 24 , 25 ]. The risk of imported malaria depends on malaria endemicity at the destination, the number and the behavior (adherence to personnel protective measures) of the travellers to risk areas, adequate use of chemoprophylaxis, and efforts for vector control around the accommodation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Amsterdam the decline in number of cases observed up until 2002 were attributed to a decrease in nonimmune patients [18]. However, this was followed by an increase in the Netherlands most notably since 2013 and mostly due to immigration of asylum seekers from the horn of Africa and among VFRs [19]. An increasing trend in malaria cases between 1973 and 2013 was also seen in the US, a country with a similar epidemiology to the UK where malaria affected mostly VFRs and travellers to Africa, specifically Nigeria [20].…”
Section: Discussionmentioning
confidence: 99%
“…A sharp increase in malaria notifications occurred in 2014, coinciding with a large influx of newly arriving refugees in Germany. Roggelin et al [ 6 ] reported an increase of vivax malaria in 2014–2015 in refugees from Eritrea admitted to the University Medical Centre in Hamburg [ 6 , 7 ], as also described in Sweden in 2014 [ 8 , Sonden et al, personal communication], and the Netherlands in 2017 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%